2021
DOI: 10.1177/0192513x211054468
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Parental Divorce and Anger, Aggression, and Hostility in Adolescents: Results of a National Lebanese Study

Abstract: To evaluate the association between divorce and aggression patterns (physical and verbal aggression and hostility) in Lebanese adolescents. This cross-sectional study enrolled 1810 (90.5%) students (January–May 2019) using a proportionate random sample of participants aged 12–17 years, drawn from private schools of all Lebanese districts. Parental divorce was significantly associated with more physical and verbal aggression and anger and hostility in adolescents. Significantly higher adjusted means of physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Out of 2000 questionnaires distributed, 1810 (90.5%) were completed and collected back. The methodology used has been previously described [39][40][41][42][43][44][45][46].…”
Section: Participantsmentioning
confidence: 99%
“…Out of 2000 questionnaires distributed, 1810 (90.5%) were completed and collected back. The methodology used has been previously described [39][40][41][42][43][44][45][46].…”
Section: Participantsmentioning
confidence: 99%
“…Empirical studies have identified various risk factors of aggression in adolescence [37], mainly gender (boys display more physical aggression than girls) [38,39], mental health disorders (most notably disruptive behavior disorders and attention-deficit/hyperactivity disorder (ADHD), alexithymia, anxiety and depression) [40,41], family characteristics including single-parent household and divorced parents [42], and peer factors involving parental divorce [43], peer rejection, bullying, and loneliness [44]. Moreover, during adolescence, developmentally normative changes in social relationships, including decreasing parental supervision, increasing influence of peers and engaging in new risky behaviors (e.g.…”
Section: Sa and Aggressionmentioning
confidence: 99%
“…Therefore, mental health professionals attach special importance to the study of family and marital life [2]. Differences in attitudes, beliefs, and expectations pertaining to the spousal relationship may lead to an imbalance in the marital relationship [3]. The inability to reconcile these differences may lead to divorce.…”
Section: Introductionmentioning
confidence: 99%